Compensatory justice - Chapman, John W. (John William), 1923-2008 (New York University Press, 1991)
"Began with presentations and commentaries at the meeting of The American Society for Political and Legal Philosophy held in conjunction with the annual meeting of the Association of American Law Schools in New Orleans, 5-8 January 1989"--Preface
"Began with presentations and commentaries at the meeting of The American Society for Political and Legal Philosophy held in conjunction with the annual meeting of the Association of American Law Schools in New Orleans, 5-8 January 1989"--Preface
Keywords: Compensation (Law) -- Philosophy -- Congresses.; Indemnisation -- Philosophie -- Congrès.; LAW -- International.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Compensation (Law) -- Philosophy; Gerechtigkeit; Rechtsphilosophie; Kongress; Schadensersatz; New Orleans (La., 1989); "Began with presentations and commentaries at the meeting of The American Society for Political and Legal Philosophy held in conjunction with the annual meeting of the Association of American Law Schools in New Orleans, 5-8 January 1989"--Pref.; "Multi-User"; dictionaries.; proceedings (reports); Conference papers and proceedings; Dictionaries.; Conference papers and proceedings.; Dictionnaires.; Actes de congrès.